(untitled) (Thành phố Hồ Chí Minh, 2005)
Tuyển dịch các truyện ngụ ngôn của Êdốp, Pheđrơ, Babri, Xintipư, Kirill Êpixkop, Ođom Trêritômxki, N. Pergamxki, L. Đơ Vanhxi, M. Luyte, B. Pêriê..
Keywords: Fables; Collections